An Empirical Analysis of the Factors Affecting Farmer Satisfaction Under the China Link Policy. (June 2021) - Gu, Hanlong; Liu, Yiying; Qian, Fengkui; Wang, Qiubing; Dong, Xiuru
China's urbanization has maintained a high growth rate for a long period of time, but the contradiction between urban and rural land use has become increasingly prominent. Link policy, promulgated in 2005 by the Chinese Central Government, made a positive attempt to promote the sustainable use of urban and rural land, which has attracted much attention. This article focuses on the implementation effects of this policy from the micro-perspective of farmers' satisfaction and its underlying influence factors using a structural equation model (SEM) based on a cross-sectional dataset of 280 households surveyed in Chongqing city, China. The results show that the farmers' satisfaction under the Link Policy is high, and most of the respondents are satisfied with the Link Policy at present. Furthermore, the farmers' satisfaction is affected by their expectations, perceived value, and perceived quality. Among these factors, perceived quality has the strongest positive impact on farmers' satisfaction, for which compensation equity under the Link Policy is most important to farmers. However, farmers' expectations and perceived value have a negative impact on farmers' satisfaction, which indicates that the higher the farmers' expectations and perceived value, the lower their satisfaction. In addition, there is a strong positive correlation between farmer satisfaction and farmer trust, which means that the higher the level of farmer satisfaction, the more support the farmers will give to the government. These main results have heuristic implications for policymakers to improve the Link Policy, thereby enhancing the farmers' satisfaction and thus achieving the goal of sustainable use between rural and urban land.